The first issue of InJAST available in print and online - Dolly Priatna; Kathryn A. Monk (Indonesian Journal of Applied Environmental Studies, 2020)
It is our great pleasure to announce that the very first issue of the Indonesian Journal of Applied Environmental Studies (InJAST) is now be available   in  both  print  and  online.  This journal has evolved from the Journal of Environmental Education which started in 2015, and was managed  by the Study Programme of Population and Environmental Education, Graduate Programme of Pakuan University. Because this study programme has now become the Study Programme of Environmental Management,  we have decided to establish this new journal to publish scientific articles covering broader environmental issues that are written by the  Indonesian  students  of  graduate programmes either in Pakuan and other universities or researchers. Meanwhile, the publication and management  of the Journal of Environmental Education will be transferred to another relevant faculty or study programme within Pakuan University.We intend the new InJAST to be  published in English (with abstracts  both in English and Bahasa) so that it can reach a wider readership internationally, and we hope encourage international  environmental students  and scientists working  in Indonesia or on topics of specific relevance to Indonesia,   to disseminate their research results and findings through  this journal.We are pleased to also announce that it has been agreed  in principle that this new journal will be published collaboratively between the Graduate School of Pakuan University and PERWAKU (Perhimpunan Cendikiawan Pemerhati  Lingkungan  Indonesia,  the Indonesian Association of Environmentalist Scholars). A formal Memorandum of Understanding   between  both  parties  will  be signed in the near future.In this occasion, we, as the chief editors of this new journal, would like to express our gratitude  to various parties and individuals who have supported this initiative,  especially to Prof. Dr. H. Bibin Rubini, M.Pd. (Chancellor of Pakuan University), Prof. Dr. Ing. H. Soewarto Hardhienata (Dean of Graduate School Pakuan University), and Prof. Jatna Supriatna, Ph.D. (Chairman   of   PERWAKU  Indonesia).     We would also like to express special thanks to our national and international  colleagues at Pakuan University  and     elsewhere, who have so generously offered their time as members of the editorial board of the journal.Last but not least, we hope that the Indonesian Journal  of  Applied Environmental Studies  (InJAST) will  provide new  colour and perspectives the scientific journals published by Pakuan Univeristy,  and become the vehicle of choice for environmental  science students  and scientists to disseminate of their work.